Intervenciones de enfermería en paciente con secuelas por traumatismo craneoencefálico - Carranza Vargas, Maholy Dayana (2024)
Traumatic brain injury (TBI) represents one of the leading causes of morbidity and mortality in the world population. Immediate and appropriate care of TBI patients is crucial to improve their outcomes and reduce sequelae. The present study focused on applying nursing care in a patient with sequelae due to traumatic brain injury through the nursing care process favoring her functional recovery and quality of life. To this end, a systematic approach was adopted, using assessment tools such as Marjory Gordon's functional patterns, which made it possible to identify and prioritize the most relevant diagnoses, among which ineffective respiratory pattern, impaired physical mobility and impaired verbal communication were highlighted. Based on these nursing diagnoses, goals and expected results were established, outlining a clear path for nursing interventions according to the patient's needs, based on scientific evidence and best practices in the clinical setting together with the NANDA-NOC-NIC taxonomies, obtaining the expected results through an individualized approach.